Pencurian Cryptocurrency oleh Aktor Negara sebagai Strategi Hybrid Warfare: (Studi Kasus Kelompok Lazarus) - Muhammad Asnul Husadi; Nur Isdah Idris (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study analyzes state-sponsored cryptocurrency theft, focusing on the Lazarus Group affiliated with North Korea, within the framework of contemporary hybrid warfare strategy. Employing a qualitative case study approach, the article explains how systematic and large-scale crypto asset theft conducted by Lazarus Group serves not only financial motives but also functions as a strategic tool to evade international sanctions and fund North Korea’s nuclear programs. The research finds that such cybercrimes reflect high-ambiguity, non-conventional tactics key features of hybrid warfare. This study expands the traditional concept of hybrid warfare by incorporating digital financial crimes as instruments of state geopolitical strategy. It further highlights the importance of international collaboration and strengthened cybersecurity policy to address increasingly complex digital-era threats.